Pelatihan dan Percontohan Aplikasi RAS dan Fitobiotik untuk Pokdakan Pembenihan Kepiting Bakau Bahari Sakti, Tanjungpinang - Dinamella Wahyuningrum; Irzal Effendi; Shavika Miranti (Institut Pertanian Bogor, 2023)
This activity aims to provide knowledge, insight, and skills in the application of recirculated aquaculture system (RAS) technology and phytobiotics to members of the Bahari Sakti mud crab hatchery group on Penyengat Island, Tanjungpinang, Riau Islands. Mastery of this application is important to improve the production performance of the mud crab hatchery group which is faced with the problem of high frequency of disease attacks on broodstock and low survival rate of larvae. The activity, which includes training, piloting, and mentoring, were take place from June‒September 2022, attended by 20 participants consisting of members of the Bahari Sakti mud crab hatchery group and public. The training materials covered the technical and management aspects of mud crab hatchery, RAS application, and phytobiotics of garlic flour in broodstock and larvae rearing. Pilot methods and mentoring were conducted in the form of RAS installations and application of phytobiotics with participants. After attending the training, there was a significant increase in knowledge and insight of these three aspects by 47, 51, and 26%, respectively, for the mud crab hatchery, phytobiotic, and RAS aspects. Pilots and mentoring in the form of rearing and spawning in the RAS system with the application of phytobiotics were carried out after training at the production facility of mud crab hatchery group. Participants in the pilot and mentoring activities were quite enthusiastic, although the attendance rate of participants was only 25‒35%. The RAS application can improve the water quality of the mud crab broodstock rearing media, while for the application of phytobiotics was not evaluated.